# Let f(x) = -5x - 4 and g(x) = 6x - 7. Find f(x) + g(x)?

**Solution:**

Given, functions are f(x) = -5x - 4

g(x) = 6x - 7

We have to find f(x) + g(x)

f(x) + g(x) = (-5x - 4) + (6x - 7)

= -5x - 4 + 6x - 7

Grouping of common terms,

= -5x + 6x - 4 - 7

= x - 11

Therefore, f(x) + g(x) = x - 11

**Example:**

Let f(x) = 2x - 4 and g(x) = 3x - 2. Find f(x) + g(x)?

**Solution:**

Given, f(x) = 2x - 4

g(x) = 3x - 2

We have to find f(x) + g(x)

f(x) + g(x) = (2x - 4) + (3x - 2)

= 2x - 4 + 3x - 2

Grouping of common terms,

= 2x + 3x - 4 - 2

= 5x - 6

Therefore, f(x) + g(x) = 5x - 6.

## Let f(x) = -5x - 4 and g(x) = 6x - 7. Find f(x) + g(x)?

**Summary:**

Let f(x) = -5x - 4 and g(x) = 6x - 7, then f(x) + g(x) = x - 11.

Math worksheets and

visual curriculum

visual curriculum